Non-targeted Metabolomics Analysis of Key Characteristic Components in Liudong Tea - ZHAO Jie, LI Furong, LIU Wenwen, MA Jiangming, QIN Jiashuang, CHEN Yan, WANG Xu (Shipin Kexue)
This study employed non-targeted metabolomics combined with chemometrics to investigate the effects of different manufacturing processes, harvest times and cultivation methods on the key characteristic components of Liudong tea, a specialty tea cultivar from Guangxi. A total of 23 key components were identified, including (+)-gallocatechin and theaflavinmonogallates. Among them, catechins and their derivatives, as well as flavonoids, predominated, accounting for 82.6% of the total. The key characteristic components with the highest variable importance in the projection (VIP) values for distinguishing Liudong tea from different processing methods and harvest times were terpenes and their derivatives, namely acuminoside@RT 9.77 and (+/-)-sabinene@RT 10.11, while that for distinguishing Liudong tea from different cultivation methods was (+)-catechin. The results indicated that different processing methods, harvest times and cultivation patterns significantly influenced the key characteristic components and their content distribution in Liudong tea. The black tea processing method promoted the formation of theaflavinmonogallates and the hydrolysis of terpenoid glycosides. The later the harvest date, the higher the relative abundance of five key flavonoid components, including kaempferol-3-O-(6’’’-trans-p-coumaroyl-2’’-glucosyl) rhamnoside. Artificial cultivation reduced the relative abundance of some key characteristic components including catechins such as (+)-catechin and their derivatives. This study contributes to understanding the mechanisms underlying the formation of the characteristic quality of different Liudong tea, thereby providing a scientific basis for improving the cultivation techniques and processing methods for the quality control of Liudong tea.